IMPLEMENTASI STANDAR PENDIDIK DAN TENAGA KEPENDIDIKAN DALAM UPAYA PENINGKATAN MUTU PENDIDIKAN DI SMA - Sunuda, Erma; Aunurrahman, Aunurrahman; Wahyudi, Wahyudi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThis study aims to obtain information about educators and educational standar in an effort to improve the quality of education in SMA Negeri 1 Ngabang, include : Planning, coordinating, controlling, evaluating and the factors of educational improving.This research is a qualitative research.Techniques data collection used include : observation, in-depth interviews and documentation. Source of data is comprised of the principle or headmaster, the administration, and teachers. The informan selected were informants who are considered to provide an accurate and in-depth information relating to this research. Checking the validity of the findings made by the number check, the adequacy of reference, and triangulate. Analysis of the data used is qualitative analysis is to describe and interpret the data.The result of the following conclusions:(1) the planning, It has done well by the headmaster. Planning is made with the intermediate school side, among other, the principal in assisted by the vice principals and coordinated well with teacher and administrative staffs. (2)Implementation is done well and effectively. (3) Controlling done by looking at the completeness of teachers administration. (4)Evaluation done well by the principal once every three months. Evaluation conducted every semester is supervisions.(5)There are still some subject that is not according with the educationalÂ Keywords:Implementation, Educator and Education Standards, Planning, Coordinating